The Role Of BOPO In Moderating The Effect Of NIM On Profit Growth In State-Owned Banks - Rahmayani Rahmayani; Edy Jumady; Ruddin (International Journal of Education Management and Religion, 2026)
This study examines the role of the Operating Expenses to Operating Income ratio (BOPO) in moderating the effect of Net Interest Margin (NIM) on profit growth in state-owned banks in Indonesia. Banking profitability is not only determined by interest margin performance but also by operational efficiency, making BOPO a critical contextual factor in explaining profit growth dynamics. The population consists of four state-owned banks listed on the Indonesia Stock Exchange, observed over the period 2013–2023. Using a saturated sampling technique, the study analyzes 44 annual financial report observations. The research applies a quantitative approach with panel data regression and Moderated Regression Analysis (MRA). The results indicate that NIM has a positive and significant effect on profit growth, showing that higher interest margin management contributes directly to increased profitability. Furthermore, the interaction term between NIM and BOPO is statistically significant, confirming that BOPO acts as a moderating variable that strengthens the relationship between NIM and profit growth. This finding implies that the positive impact of NIM on profit growth becomes stronger when banks operate more efficiently in controlling operating costs relative to operating income. The study highlights the importance of integrating margin management and operational efficiency strategies to enhance sustainable profit growth in state-owned banking institutions.